Hubungan Pengetahuan Gizi Terhadap Kejadian Anemia pada Remaja Putri di SMP Negeri 13 Kota Jambi - Safitri Safitri; Sri Maharani (Universitas Baiturrahim, 2019)
Anemia is a major public health problem in the world with the highest prevalence in developing countries. Anemia of 80-90% occurs in preschoolers and girls. The prevalence of anemia in adolescent girls (5-14 years) is 26.7% and aged 15-24 years is 18.4%. This study is a quantitative study, with a cross sectional design that aims to determine the relationship of nutritional knowledge to the incidence of anemia in adolescent girls in SMP Negeri 13 Kota Jambi. Knowledge data collection using a questionnaire and the incidence of anemia is known through hemoglobin examination using Easy Touch GHb. 50 research subjects were selected by proportional random sampling. This study was analyzed using the chi square statistical test. The results of the study there is a relationship between knowledge of nutrition to the incidence of anemia in adolescent girls in SMP Negeri 13 Kota Jambi (p-value = 0.035 <alpha 0.05). From the results of this study it is expected that the SMP Negeri 13 collaborates with the Tahtul Yaman Public Health Center in providing education through counseling to increase knowledge about balanced nutrition diets for girls.